Marital Failure As a Social Reality in Sidney Sheldon’s Novel The Other Side of Midnight - ., Hidayati; ., Zuindra; ., Arifuddin; ., Aflina; MZ, Zainab (KnE Social Sciences, 2019)
This research deals with literary works as a medium for conveying reality of social problems through Sydney Sheldon’s novel The Other Side of Midnight. One of the issues depicted in the novel is marital failure. The husband, as one of the characters in the novel, has a prestigious job, a pilot; and with an appealing appearance, he easily gets beautiful women around him. There are some various causal factors as the triggers of marital failure such as infidelity, career, selfishness, social welfare, age education, and financial problems; however in this research, the causal factors of marital failure discussed are triggered by infidelity, career, and selfishness. The method used is mixed, qualitative and quantitative. The combination of both designs provides a more detailed description, information and understanding of the object of study. Quantitative method is related to numerical variables which are further described through qualitative design. The number of respondents is 40 and selected randomly in Medan city. The social and cultural background is adapted to the object of research. The results show that there are three main factors causing marital failure in the novel: infidelity, career and selfishness. The findings of the research are in line with the field research. 97.5% of respondents agree that literary work is a medium for disclosing social problems; 2.5% express support. In the case of marital failure as a social problem, 97.5 respondents state a strong agreement and 2.5% express support. In things related to the trigger of marital failure: infidelity, career and selfishness, 100% of respondents strongly agree. Keywords: marital failure, infidelity, career, selfishness